Knowledge and awareness of stem cells among expectant mothers and parents of elementary school children in Bareilly and Delhi cities - Mayank Kumar Saran; Nagesh Lakshminarayan; Manish Kumar; G Shanmukha (Wolters Kluwer Medknow Publications, 2015)
Introduction: Stem cells are clonogenic cells capable of both self-renewal and multi-lineage differentiation. Stem cells have been isolated from various tissues, including umbilical cord blood, bone marrow, neural tissue, skin, retina, and dental pulp tissue. Objectives: To assess the knowledge and awareness about stem cells and dental stem cells among expectant mothers and parents of elementary school children in Bareilly and Delhi cities. Materials and Methods: A cross-sectional survey was conducted in which a close-ended questionnaire proforma was given to a sample of 1009 subjects who are parents of elementary school children and expectant mothers from Bareilly and Delhi cities. After 1-week, the filled questionnaire proforma was collected back from the school children and expectant mothers. The results were analyzed using Chi-square test. Results: Out of a sample of 1009 subjects, 809 were from Bareilly (401 expectant mothers and 408 parents of elementary school children) and remaining 200 from Delhi (104 were expectant mothers and 96 parents of elementary school children). The awareness about stem cells was 25% from Delhi and 18% from Bareilly and this difference was statistically significant. Conclusion: The awareness regarding stem cells and dental stem cells was generally poor among the parents of elementary school children and the expectant mothers. It is time to develop and cater programs to improve the awareness related to stem cells as stem cell therapy is said to have immense potential.